Control of browning in plant tissue culture: A review - Amente, Gerema; Chimdessa, Emiru (Journal of Scientific Agriculture, 2021)
Browning is one of the severe problems in plant tissue culture that hampers successful in vitro propagation of plants especially woody and perennial plants. In order to control the browning problem, different efforts has been made in vitro such as presoaking of explants in antioxidant solution, incorporation of antioxidants into medium, culturing in the dark period and frequent subculturing of explants. Presoaking of explants in antioxidant solutions like polyvinylpyrolidone (PvP) and ascorbic acid (AC) is one of the most frequently used. Incorporation of antioxidants such as 0.2-0.5g/l PvP and 15-250mg/l ascorbic acid into MS medium is commonly used to control browning in different plants and explants followed by activated charcoal, citric acid, MES and AIP. Moreover, frequent sub culturing and incubation of explants in the dark period is the other alternative. This review article includes the study of previous and current research achievements in a comprehensive way on the different methods to control browning problem in plant tissue culture and suggests further optimization for successful control of browning when using the same or different crops as well explants.